Efficacy of Hyaluronic Acid Gel as an Adjunct to Non-Surgical Periodontal Treatment in Smokers with Periodontitis: A Retrospective Case Control Study - (:unkn) unknown (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: To investigate the clinical effectiveness of adjunctive hyaluronic acid (HA) application to non-surgical periodontal treatment (NSPT) on periodontal parameters and gingival crevicular fluid (GCF) volume in smoking patients with stage III and grade C periodontitis. Methods: Records of patients who underwent previously NSPT with or without HA gel application were reviewed. The clinical examinations and radiographs of patients, which were collected, are used as data. At baseline, 1 and 3 months, periodontal parameters such as plaque index (PI), gingival index (GI), bleeding on probing (BOP), probing depth (PD) and clinical attachment level (CAL), and GCF volume were assessed. Results: Total 20 patients (male/female: 15/5) were included in the study who met the eligibility criteria. For 10 of these patients only NSPT was performed (Control group), the other 10 patients received NSPT with HA gel application (Test group). Intra-group differences in both groups were significant in periodontal parameters: PI (both, p<0.001), GI (both, p<0.001), BOP (both, p<0.001), PD (both, p<0.05) and CAL (both, p<0.05); and in GCF volume (both, p<0.05). No statistically significant differences were determined between the treatment groups at any assessment time periods in any outcomes (all, p>0.05) nor in the changes (Delta) with time (all, p>0.05). Conclusion: Compared to NSPT alone, the application of HA as adjunct to NSPT did not have any additional clinical effectiveness in smokers having periodontitis.
Keywords: Gingival crevicular fluid; hyaluronic acid; periodontitis; root planing; LOCALLY DELIVERED DOXYCYCLINE; SMOKING; GLYCOSAMINOGLYCANS; THERAPY; DEFECTS; BONE; DEBRIDEMENT; GINGIVITIS; SURGERY